Iron ion silicon-based adsorbing material as well as preparation method and application thereof

By modifying and grafting high-selective ligands on the surface of silicon balls, iron ion silicon-based adsorption materials are prepared, which solves the problem of difficult to remove trace iron impurities in rare earths in the prior art, and achieves efficient and economical iron ion adsorption and removal effect.

CN119425609AActive Publication Date: 2025-02-14GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411705394.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove trace iron impurities during the rare earth separation and purification process, and the commonly used iron removal methods have problems such as poor selectivity, high production costs, and complex equipment.

Method used

By selecting silicon spheres as the substrate of adsorption material, modifying the surface of its surface using vinyl silane coupling agent, and grafting the highly selective ligand to the surface by grafting method, an iron ion silicon-based adsorption material was prepared, and the use of this The selective effect on iron ions can achieve directional adsorption and removal of iron impurities in rare earth solutions.

Benefits of technology

The iron ion adsorption capacity is significantly improved, and the efficient removal of trace iron ions in rare earth solutions is achieved. The process is simple, the cost is low, and it has good adsorption selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154403380000021
    Figure BDA0005154403380000021
  • Figure BDA0005154403380000061
    Figure BDA0005154403380000061
  • Figure BDA0005154403380000081
    Figure BDA0005154403380000081
Patent Text Reader

Abstract

The invention relates to an iron ion silicon-based adsorbing material as well as a preparation method and application thereof. The iron ion silicon-based adsorption material is prepared by the following steps: S1, coupling vinyl silane to the surface of a silicon ball to obtain a modified silicon ball; and S2, copolymerizing the modified silicon balls with an acrylic monomer and a cross-linking agent to obtain the iron ion silicon-based adsorption material. The iron ion silicon-based adsorbing material disclosed by the invention has relatively high adsorption capacity and excellent adsorption selectivity on iron ions, the adsorption capacity of the iron ions is obviously improved, directional adsorption removal of iron impurities in a rare earth solution is realized, and a simple, convenient and efficient method is provided for removing trace iron ions in the rare earth solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of adsorption material preparation technology and rare earth element separation and purification, and relates to an iron ion silicon-based adsorption material and a preparation method and application thereof. Background Art

[0002] Iron is widely present in rare earth minerals and is one of the most common impurities. The presence of iron has a great impact on the product performance, quality and effect of downstream rare earth high-end functional materials. For example, iron impurities have a strong quenching effect on the luminescence performance of phosphors, reduce the optical properties of lanthanum oxide optical glass, reduce the dielectric constant of rare earth oxides, increase leakage current, and deteriorate dielectric properties. Therefore, reducing the iron impurity content in rare earths is particularly important for improving the quality of rare earth high-precision products.

[0003] The commonly used iron removal methods in the rare earth separation and purification process are chemical precipitation, solvent extraction and ion exchange. Chemical precipitation has the advantages of low production cost and easy operation, but poor selectivity and difficulty in forming precipitation for low-concentration iron impurities, and cannot achieve deep removal of trace iron impurities. Solvent extraction has the advantages of high production efficiency and good selectivity, but when it is used for deep removal of iron impurities, it requires multiple stages and complex equipment. Ion exchange has the advantage of good iron removal depth, but high loss of main elements, low yield, and long production cycle.

[0004] The adsorption method uses the different binding abilities of organic ligands and ions to achieve separation. During the contact between the functionalized adsorption material and a solution containing a variety of mixed ions, the target ions are adsorbed into the solid phase material. This method has the advantages of high efficiency, environmental protection, high selectivity and easy desorption. In recent years, it has become the most effective means of preparing high-purity rare earths.

[0005] CN101711975A discloses an iron ion imprinted silica gel, which uses mercaptopropylsilane as a functional monomer and is prepared using iron ions as a template using molecular imprinting synthesis technology, and can selectively enrich trivalent iron ions (Fe(III)). CN104130440A discloses a method for preparing an iron ion imprinted polymer, wherein iron ions are used as templates, acrylamide is used as a functional monomer, and an iron ion imprinted polymer is synthesized using ion imprinting preparation technology, and the product has a high adsorption capacity and good adsorption selectivity for iron ions. CN104130440A discloses a method for preparing an iron ion imprinted polymer, wherein iron ions are used as templates, acrylic monomers are used as functional monomers, and an iron ion imprinted polymer is synthesized using ion imprinting preparation technology, and the obtained iron ion imprinted polymer has a porous structure composed of small particles inside, and a high iron removal rate that can reach more than 90%. Summary of the invention

[0006] The inventors studied the iron ion imprinted adsorption materials reported in CN101711975A, CN104130440A and CN110407976A and found that although they have a certain selectivity for iron ions, they have low adsorption capacity, complex preparation process and high cost, so it is necessary to develop new adsorption materials.

[0007] The present invention selects silicon spheres as adsorption material substrates, uses a silane coupling agent to modify the surface thereof, and then grafts a highly selective ligand onto the surface thereof by chemical bonding, and utilizes the selective effect of the ligand on iron ions to compensate for the defect of poor selectivity of the adsorption material, thereby preparing an iron ion silicon-based adsorption material, significantly improving the iron ion adsorption capacity and realizing directional adsorption and removal of iron impurities in a rare earth solution.

[0008] The present invention modifies the surface of silicon spheres by a grafting method to obtain an iron ion silicon-based adsorption material, which has a high adsorption capacity and excellent adsorption selectivity for iron ions, and provides a simple, convenient and efficient method for removing trace iron ions in rare earth solutions.

[0009] In one aspect, the present invention provides a method for preparing an iron ion silicon-based adsorption material, comprising:

[0010] S1, surface modification of silicon spheres: coupling vinyl silane to the surface of silicon spheres to obtain modified silicon spheres;

[0011] S2, copolymerization: copolymerizing the modified silica spheres with acrylic monomers and crosslinking agents to obtain iron ion silicon-based adsorption materials.

[0012] Step S1

[0013] In step S1, vinylsilane is first hydrolyzed into silanol, and then condenses with the hydroxyl groups on the surface of the silicon sphere and dehydrates, thereby coupling to the surface of the silicon sphere.

[0014] Vinylsilane is a silane containing a vinyl group in the molecule, which can be represented by the structure shown in the following formula I:

[0015]

[0016] wherein R1 is C1-C4 alkoxy or C1-C4 alkoxy substituted C1-C4 alkoxy, in particular C1-C2 alkoxy or C1-C2 alkoxy substituted C1-C2 alkoxy;

[0017] R2 and R3 are each independently selected from C1-C4 alkoxy, C1-C4 alkoxy substituted C1-C4 alkoxy and C1-C4 alkyl, in particular C1-C2 alkoxy, C1-C2 alkoxy substituted C1-C2 alkoxy and C1-C2 alkyl.

[0018] In some embodiments, the vinyl silane is selected from vinyl trimethoxysilane, vinyl triethoxysilane, vinyl triisopropoxysilane, vinyl tri(2-methoxyethoxy)silane, vinyl methyl dimethoxysilane, vinyl methyl diethoxysilane.

[0019] In step S1, the usage ratio of the vinyl silane to the silicon spheres may be 1 to 2 mL of vinyl silane / g of silicon spheres, but is not limited thereto.

[0020] In step S1, the coupling reaction is carried out in a solvent, and the solvent can be any solvent that does not affect the coupling reaction, such as water, methanol, ethanol, acetone, toluene, dimethylformamide, dimethyl sulfoxide or a combination thereof, such as a mixture of water and methanol or ethanol, but is not limited thereto.

[0021] In step S1, the temperature of the coupling reaction is not particularly limited, and can be room temperature to 90° C., preferably 50 to 90° C. There is no particular restriction on the reaction time. When the temperature is low, the required reaction time is long, while when the temperature is high, it is conducive to accelerating the reaction speed. Generally speaking, the reaction time can be more than 2 hours, for example, 6 to 48 hours.

[0022] In some embodiments, step S1 further comprises, after the coupling reaction is completed, performing solid-liquid separation, washing and drying the solid to obtain modified silicon spheres.

[0023] The method of solid-liquid separation is not limited, for example, it can be centrifugation, normal pressure filtration, reduced pressure filtration (such as suction filtration), etc., but it is not limited thereto.

[0024] The washing can be carried out by any suitable method as long as the reaction by-products can be removed, for example, a solvent and / or water can be used for washing.

[0025] The drying method is not particularly limited, and vacuum drying or the like may be employed.

[0026] In some cases, there are some adsorbed impurities on the surface of the silica spheres used, which affect the coupling reaction.

[0027] Therefore, in some embodiments, step S1 further includes a step of activating the silica spheres before the coupling reaction.

[0028] There is no particular limitation on the method of activating the silicon spheres, as long as the surface groups of the silicon spheres can be activated to facilitate the coupling reaction, for example, by acid leaching, high temperature calcination, etc.

[0029] In some embodiments, the activation of the silicon spheres is performed by acid leaching. For example, after the silicon spheres are soaked in an acid solution, they are washed to neutrality and dried. The acid solution may be hydrochloric acid, sulfuric acid or nitric acid, the molar concentration of the acid solution is preferably 1 to 6 mol / L, the amount ratio of the silicon spheres to the acid is preferably 5 to 20 mL of acid per gram of silicon spheres, the acid leaching time may be 24 to 72 hours, the drying temperature is preferably 40 to 80°C, the time is preferably 8 to 24 hours, preferably under reduced pressure, but the present invention is not limited thereto.

[0030] There is no particular limitation on the particle size of the silicon spheres as long as they can be used as an adsorbent material. For example, the particle size of the silicon spheres can be 500-500 mesh, 100-200 mesh, etc.

[0031] Step S2

[0032] In step S2, acrylic monomers are used as functional monomers, and functional polymer materials are grafted onto the surface of modified silicon spheres by copolymerization with vinyl silane, thereby preparing iron ion silicon-based adsorption materials.

[0033] The acrylic monomer may be selected from acrylic acid, methacrylic acid, ethylacrylic acid, propylacrylic acid, phenylacrylic acid, benzylacrylic acid, etc., and is preferably acrylic acid.

[0034] The usage ratio of acrylic monomer to modified silicon sphere can be 1-27 mol acrylic monomer / g modified silicon sphere, for example 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26 mol acrylic monomer / g modified silicon sphere, preferably 9-27 mol acrylic monomer / g modified silicon sphere.

[0035] The crosslinking agent may be a monomer containing two vinyl groups in the molecule, such as a diacrylate monomer, a dimethacrylate monomer, divinylbenzene, and a diacrylamide monomer, but is not limited thereto. In some embodiments, the crosslinking agent is selected from ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, pentaethylene glycol dimethacrylate, divinylbenzene, and N,N-methylenebisacrylamide, preferably ethylene glycol dimethacrylate.

[0036] The copolymerization can be initiated by an initiator. Any suitable initiator can be used without particular limitation. For example, the initiator can be a thermal initiator, such as an azo initiator, a peroxide initiator or a persulfate initiator, such as azobisisobutyronitrile, ammonium persulfate, potassium persulfate, benzoyl peroxide, etc., preferably ammonium persulfate. In the case of a thermal initiator, the copolymerization temperature can be 50 to 100°C, and the time is preferably 1 to 48 hours. The specific temperature and time can be determined by conventional time according to the initiator used and its dosage. In addition, the copolymerization is usually carried out under a protective gas atmosphere to eliminate the negative effects of oxygen on the polymerization reaction. The protective gas can be nitrogen, helium, neon or argon, preferably nitrogen.

[0037] The copolymerization can be carried out in a solvent. There is no particular limitation on the solvent, as long as it does not significantly adversely affect the polymerization. In some embodiments, the solvent can be water, methanol, ethanol, toluene, dimethyl sulfoxide, or a combination thereof, but is not limited thereto.

[0038] In some embodiments, step S2 further comprises, after the copolymerization reaction is completed, performing solid-liquid separation, washing and drying the solid to obtain the iron ion adsorption material.

[0039] The method of solid-liquid separation is not limited, for example, it can be centrifugation, normal pressure filtration, reduced pressure filtration (such as suction filtration), etc., but it is not limited thereto.

[0040] The washing can be carried out by any suitable method as long as the reaction by-products can be removed, for example, a solvent and / or water can be used for washing.

[0041] The drying method is not particularly limited, and vacuum drying or the like may be employed.

[0042] The vacuum drying temperature is preferably 40 to 80°C, and the temperature is preferably 8 to 24 hours.

[0043] Another aspect of the present invention provides an iron ion silicon-based adsorption material prepared by the above method.

[0044] Experiments show that the iron ion silicon-based adsorption material of the present invention can selectively adsorb iron ions from the rare earth solution and remove trace iron ion impurities in the rare earth solution.

[0045] Therefore, another aspect of the present invention provides use of the iron ion silicon-based adsorption material of the present invention for removing iron ions from a rare earth solution.

[0046] Another aspect of the present invention provides a method for removing iron ions from a rare earth solution, the method comprising the step of contacting the rare earth solution with the iron ion silicon-based adsorption material of the present invention. By contacting the rare earth solution with the iron ion silicon-based adsorption material of the present invention, the iron ion silicon-based adsorption material of the present invention can selectively adsorb iron ions from the rare earth solution, thereby separating the iron ions from the rare earth element ions.

[0047] The iron ion in the present invention refers to the Fe(III) ion.

[0048] The rare earth solution in the present invention refers to a solution containing rare earth elements. The rare earth elements are III-valent and are selected from one or more of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), promethium (Pm), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), yttrium (Y), and scandium (Sc).

[0049] Beneficial effects:

[0050] 1) The present invention uses acrylic acid as a functional monomer and grafts it on the surface of modified silicon spheres to prepare an iron ion silicon-based adsorption material, thereby achieving the purpose of selectively adsorbing iron ions and providing a simple new method for selective separation of iron ions in rare earth solutions;

[0051] 2) The iron ion silicon-based adsorption material of the present invention has the advantages of fast adsorption rate, good iron removal depth, high adsorption selectivity and simple preparation method. It can reach adsorption equilibrium within 45 minutes, and can reduce iron ions from 60 mg / L to below 0.2 mg / L. It has excellent selectivity for iron ions in rare earth solutions, and removes iron ions to below 0.3 mg / L while not adsorbing or low adsorbing rare earth ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is an infrared spectrum of the activated silicon sphere ASG and the obtained iron ion silicon-based adsorption material in Example 2 of the present invention.

[0053] Figure 2 The effect of different oscillation times on the iron adsorption capacity of the iron ion silicon-based adsorption material synthesized in Example 2 of the present invention is shown.

[0054] Figure 3 The effect of the iron ion silicon-based adsorption material synthesized in Example 2 of the present invention on the iron ion adsorption capacity at different initial iron ion concentrations is shown.

[0055] Figure 4 The effect of the iron ion silicon-based adsorption material synthesized in Example 2 of the present invention on the iron ion adsorption capacity at different solid-liquid ratios is shown. DETAILED DESCRIPTION

[0056] To facilitate understanding of the present invention, the technical solution of the present invention is further described below in conjunction with embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0057] Example

[0058] Reagents and equipment

[0059] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0060] Microsphere silica gel was purchased from Macklin (Cat. No. C875066), with a particle size of 100-200 mesh and a specific surface area of ​​400-500 m 2 / g.

[0061] Vinyltrimethoxysilane, structural formula Purchased from Aladdin.

[0062] Acrylic acid monomers were purchased from Adamas.

[0063] Ethylene glycol dimethacrylate, structural formula Purchased from Macklin.

[0064] The contents of iron ions and rare earth elements in the solution were determined by inductively coupled plasma atomic emission spectrometry ICP-OES (instrument model: PQ9000, manufacturer: Jena).

[0065] Infrared spectra were measured on a Fourier transform infrared spectrometer (instrument model: IS-5, manufacturer: Thermo Fisher Scientific, USA).

[0066] Example 1

[0067] 50 g of coarse-porous microsphere silica gel was placed in 500 mL of 3 mol / L hydrochloric acid aqueous solution and soaked for 48 h. The mixture was repeatedly washed with distilled water until neutral, filtered, and vacuum dried to obtain activated silica spheres ASG.

[0068] Take 10g of activated silica balls and place them in 100mL of 50% ethanol aqueous solution, add 10mL of vinyltrimethoxysilane (VTMS), and continue stirring the reaction at 50°C for 24h. After the reaction is completed, wash repeatedly with ethanol and distilled water, filter, and vacuum dry to obtain the product ASG-VTMS.

[0069] Take 18 mol of acrylic acid (AA) and place it in 100 mL of 50% ethanol aqueous solution, add 2.5 g of ASG-VTMS, stir for 2 h, then add 1.5 mL of ethylene glycol dimethacrylate and 1 mmol of ammonium persulfate, and continue stirring and reacting at 60 ° C in a nitrogen atmosphere for 24 h. After the reaction is completed, wash repeatedly with ethanol and distilled water, filter, and vacuum dry to obtain an iron ion silicon-based adsorption material.

[0070] The adsorption performance test of the adsorbent material prepared in this embodiment is carried out as follows: 10 mg of the prepared adsorbent material is weighed and added to 20 mL of a 20 mg / L FeCl3 solution, and the mixture is shaken at 300 r / min for 90 min at 30°C, the adsorbent material is filtered to collect the filtrate, and the iron ion content in the filtrate is determined. The adsorption capacity of the iron ion adsorbent material is calculated by calculating the reduction in the amount of iron ions in the solution before and after adsorption. The adsorption capacity Q of the adsorbent material is calculated according to formula (1).

[0071]

[0072] Where, Q represents the adsorption capacity (mg / g), c i With c e Respectively represent the initial concentration and equilibrium concentration of iron ions (mg / L), V represents the volume of the solution (L), and m represents the amount of adsorption material (g).

[0073] The test results show that the adsorption capacity of the adsorption material prepared in this example for Fe(III) is 23.41 mg / g, indicating that the obtained product has good adsorption performance for Fe(III).

[0074] Example 2

[0075] Take 27 mol of acrylic acid (AA) and place it in 100 mL of 50% ethanol aqueous solution, add 2.5 g of ASG-VTMS prepared in Example 1, stir for 2 h, then add 2.65 mL of ethylene glycol dimethacrylate and 1 mmol of ammonium persulfate, and continue stirring and reacting at 60 ° C. in a nitrogen atmosphere for 24 h. After the reaction is completed, wash repeatedly with ethanol and distilled water, filter, and vacuum dry to obtain an iron ion silicon-based adsorption material.

[0076] The infrared spectra of the activated silicon spheres ASG prepared in Example 1 and the iron ion silicon-based adsorption material obtained in this example were measured. Figure 1 shown.

[0077] Figure 1In the infrared spectra of activated silicon sphere ASG and the obtained iron ion silicon-based adsorption material, three Si-O-Si characteristic peaks appeared, and there was no obvious change in the peak position before and after grafting, proving that grafting did not affect the chemical structure of the silicon sphere substrate. In addition, C=O and CH characteristic peaks appeared in the infrared spectrum of the iron ion silicon-based adsorption material, which are characteristic peaks that do not appear in the raw material ASG, indicating that acrylic acid is successfully attached to the surface of the silicon sphere.

[0078] Example 3

[0079] This example investigates the effect of different oscillation times on the adsorption capacity of the iron ion silicon-based adsorption material.

[0080] 10 mg of the iron ion silicon-based adsorbent material synthesized in Example 2 was weighed separately, added to 20 ml of 20 mg / L FeCl3 solution, and then placed at 30°C and oscillated at 300 r / min for different times. The adsorbent material was filtered to collect the filtrate, the iron ion content in the filtrate was determined, and the adsorption capacity Q was calculated according to formula (1) in Example 1.

[0081] The test results are as follows Figure 2 As shown, the adsorption material has fast adsorption kinetics. The adsorption capacity increases rapidly at first and then tends to be flat, and finally reaches adsorption equilibrium at 45 minutes, with an adsorption capacity of up to 24.34 mg / g.

[0082] Example 4

[0083] This example investigates the effect of different concentrations of FeCl3 solution on the adsorption capacity of the iron ion silicon-based adsorption material.

[0084] 10 mg of the iron ion silicon-based adsorption material synthesized in Example 2 was weighed separately, added to 20 ml of FeCl3 solution of different concentrations, and then placed at 30°C and oscillated at 300 r / min for 45 min. The adsorption material was filtered to collect the filtrate, the iron ion content in the filtrate was determined, and the adsorption capacity Q was calculated according to formula (1) in Example 1.

[0085] The test results are as follows Figure 3 As shown in the figure, with the increase of the initial concentration of iron ions, the adsorption capacity of the adsorbent material first increases rapidly and then tends to be flat. When the iron ion concentration reaches 54 mg / L, the adsorption of the adsorbent material reaches saturation, and the maximum adsorption capacity can reach 43.71 mg / g.

[0086] Example 5

[0087] This example investigates the effect of different solid-liquid ratios on the adsorption capacity of the silicon-based adsorption material for iron ions.

[0088] Different masses of the iron ion silicon-based adsorbent material synthesized in Example 2 were weighed according to the solid-liquid ratio of 0.5, 1, 2, 3, 4, and 5 g / L, respectively, added to 20 ml of 60 mg / L FeCl3 solution, and then placed at 30°C and shaken at 300 r / min for 45 min. The adsorbent material was filtered to collect the filtrate, the iron ion content in the filtrate was determined, and the adsorption capacity Q was calculated according to formula (1) in Example 1.

[0089] The test results are as follows Figure 4 When the solid-liquid ratio is greater than 3g / L, the iron ion removal rate reaches more than 99%, and the highest can reach 99.70%. The iron ions can be reduced from 60mg / L to below 0.2mg / L, indicating that the obtained product has a good iron removal depth for Fe(Ⅲ).

[0090] Example 6

[0091] This example investigates the selective adsorption performance of iron ions by the iron ion silicon-based adsorption material for iron ions in a rare earth solution.

[0092] A rare earth solution containing about 4 mg / L Fe(III) (excluding Sc and Pm, and the concentrations of the remaining rare earth ions La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Y are respectively about 20 mg / L) is prepared as follows: 15 single rare earth chloride solutions and ferric chloride solution of known concentrations are taken into a volumetric flask according to the amounts calculated based on the given concentrations, and then diluted to the scale with distilled water.

[0093] Weigh 10 mg of the iron ion silicon-based adsorption material synthesized in Example 2, add 10 ml of rare earth solution, and place it at 30°C and oscillate at 300 r / min for 45 min. Filter the adsorption material to collect the filtrate, determine the iron ion and rare earth element ion content in the filtrate, and calculate the removal rate. The results are shown in Table 1.

[0094] The metal ion removal rate R is calculated according to formula (2).

[0095]

[0096] Among them, c i With c e represent the initial concentration and equilibrium concentration of metal ions (mg / L), respectively.

[0097] Table 1 Removal rate of different ions by iron ion silicon-based adsorption materials

[0098] Metal ions <![CDATA[Initial concentration c i (mg / L)]]> <![CDATA[Equilibrium concentration c e (mg / L)]]> Removal rate (%) Fe 4.234 0.2487 94.13 La 20.86 21.19 0 Ce 21.21 21.42 0 Pr 17.79 18.05 0 Nd 23.42 23.80 0 Sm 22.06 22.15 0 Eu 22.55 22.76 0 G 22.84 22.82 0 Tb 17.12 17.42 0 Dy 23.39 23.82 0 Ho 23.13 23.42 0 Er 19.17 19.22 0 Tm 22.06 22.73 0 Yb 22.67 22.67 0 Lu 22.26 22.81 0 Y 22.89 23.44 0

[0099] The iron ion silicon-based adsorption material of the present invention has excellent adsorption selectivity for iron ions in a rare earth solution. After adsorption, the iron ion concentration is reduced to below 0.3 mg / L, while the concentration of rare earth ions is not reduced. As shown in Table 1, the iron ion silicon-based adsorption material of the present invention can remove 94.13% of iron ions without adsorbing rare earth ions, thereby increasing the concentration ratio of rare earth ions to iron ions in the solution from 76.4 to 1317.7, and can achieve the removal of trace iron ion impurities in the rare earth solution.

[0100] Comparative Example 1

[0101] Take 3mmol Fe(NO3)3·9H2O and 18mol acrylic acid (AA) and place them in 100mL of 50% ethanol aqueous solution, add 2.5g ASG-VTMS prepared in Example 1, stir for 2h, then add 1.5mL ethylene glycol dimethacrylate and 1mmol ammonium persulfate, and continue stirring and reacting for 24h under a nitrogen atmosphere at 60°C. After the reaction, wash repeatedly with ethanol and distilled water, filter, and vacuum dry. Then, wash the dried sample repeatedly with HCl solution to remove template ions, and vacuum dry to obtain an iron ion imprinted adsorption material.

[0102] The adsorption material prepared in this comparative example was subjected to the same adsorption performance test as in Example 1. The test results showed that the adsorption capacity of the adsorption material prepared in this comparative example for iron ions was 10.42 mg / g, and the adsorption performance was inferior to that of Example 1.

[0103] Comparative Example 2

[0104] Take 3mmol Fe(NO3)3·9H2O and 27mol acrylic acid (AA) and place them in 100mL of 50% ethanol aqueous solution, add 2.5g ASG-VTMS prepared in Example 1, stir for 2h, then add 2.65mL ethylene glycol dimethacrylate and 1mmol ammonium persulfate, and continue stirring and reacting for 24h under a nitrogen atmosphere at 60°C. After the reaction, wash repeatedly with ethanol and distilled water, filter, and vacuum dry. Then, wash the dried sample repeatedly with HCl solution to remove template ions, and vacuum dry to obtain an iron ion imprinted adsorption material.

[0105] The adsorption material prepared in this comparative example was subjected to the same adsorption performance test as in Example 2. The test results showed that the adsorption capacity of the adsorption material prepared in this comparative example for Fe(III) was 19.56 mg / g, and the adsorption performance was inferior to that of Example 2.

[0106] The adsorption material prepared in this comparative example was subjected to the same selective adsorption performance test as in Example 6. The test results showed that the removal rate of rare earth ions by the adsorption material prepared in this comparative example was 0%, and the removal rate of iron ions was 75.25%. After adsorption, the iron ion concentration was still greater than 1 mg / L, and the iron ion removal effect was not as good as that in Example 6.

[0107] Although the iron ion imprinted adsorbent material has a certain selectivity for iron ions, its adsorption capacity is low, and the preparation process is complicated, resulting in high cost. The iron ion silicon-based adsorbent material of the present invention only adsorbs iron but not rare earth ions in the rare earth solution, and the ratio of the distribution coefficient between the target iron ions and the competing ions is very high. The excellent adsorption selectivity for iron is a significant advantage of the silicon-based adsorbent material of the present invention. In addition, the iron ion silicon-based adsorbent material of the present invention has a high adsorption capacity for iron ions, and the preparation process is simple, which reduces the cost.

[0108] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an iron ion silicon-based adsorption material, comprising: S1, surface modification of silicon spheres: coupling vinyl silane to the surface of silicon spheres to obtain modified silicon spheres; S2, copolymerization: copolymerizing the modified silica spheres with acrylic monomers and crosslinking agents to obtain iron ion silicon-based adsorption materials.

2. The method according to claim 1, characterized in that Vinyl silane is represented by the structure shown in the following formula I: wherein R1 is C1-C4 alkoxy or C1-C4 alkoxy substituted C1-C4 alkoxy, in particular C1-C2 alkoxy or C1-C2 alkoxy substituted C1-C2 alkoxy; R2 and R3 are each independently selected from C1-C4 alkoxy, C1-C4 alkoxy substituted C1-C4 alkoxy and C1-C4 alkyl, in particular C1-C2 alkoxy, C1-C2 alkoxy substituted C1-C2 alkoxy and C1-C2 alkyl; In particular, the vinylsilane is selected from vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, vinyltri(2-methoxyethoxy)silane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane.

3. The method according to claim 1, characterized in that In step S1, The ratio of the vinyl silane to the silicon sphere is 1 to 2 mL of vinyl silane / g of silicon sphere; and / or The coupling reaction is carried out in a solvent, preferably the solvent is selected from water, methanol, ethanol, acetone, toluene, dimethylformamide, dimethyl sulfoxide or a combination thereof; and / or The temperature of the coupling reaction is room temperature to 90°C, preferably 50 to 90°C; the reaction time is more than 2 hours, for example 6 to 48 hours.

4. The method according to claim 1, characterized in that: Step S1 also includes, after the coupling reaction is completed, performing solid-liquid separation, washing and drying the solid to obtain modified silicon spheres.

5. The method according to claim 1, characterized in that: Step S1 also includes a step of activating the silicon spheres before the coupling reaction, and preferably the activation of the silicon spheres is performed by acid leaching.

6. The method according to claim 1, characterized in that In step S2, The acrylic monomer is selected from acrylic acid, methacrylic acid, ethyl acrylic acid, propyl acrylic acid, phenyl acrylic acid, benzyl acrylic acid, preferably acrylic acid; and / or The usage ratio of the acrylic monomer to the modified silicon sphere is 1 to 27 mol acrylic monomer / g modified silicon sphere, preferably 9 to 27 mol acrylic monomer / g modified silicon sphere; and / or The crosslinking agent is selected from diacrylate monomers, dimethacrylate monomers, divinylbenzene, and diacrylamide monomers, preferably selected from ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, pentaethylene glycol dimethacrylate, divinylbenzene and N,N-methylenebisacrylamide, more preferably ethylene glycol dimethacrylate; and / or The copolymerization is carried out in a solvent, and the solvent is preferably selected from water, methanol, ethanol, toluene, dimethyl sulfoxide or a combination thereof.

7. The method according to claim 1, characterized in that Step S2 also includes, after the copolymerization reaction is completed, performing solid-liquid separation, washing and drying the solid to obtain the iron ion adsorption material.

8. An iron ion silicon-based adsorption material prepared by the method according to any one of claims 1 to 7.

9. Use of the iron ion silicon-based adsorption material according to claim 8 for removing iron ions from a rare earth solution.

10. A method for removing iron ions from a rare earth solution, the method comprising the step of contacting the rare earth solution with the iron ion silicon-based adsorption material according to claim 8.

Citation Information

Patent Citations

  • Method for preparing iron ion imprinted silica gel

    CN101711975A

  • Iron ion imprinting polymer as well as preparation method and application thereof

    CN110407976A

  • Preparation method for iron ion imprinted polymer

    CN104130440A

  • Preparation method of silicon dioxide / cationic polyacrylamide hybrid adsorbent

    CN106111088A

  • Functional macroporous organic silica gel material as well as preparation method and application thereof

    CN115106067A